2014
DOI: 10.1186/bf03352278
|View full text |Cite
|
Sign up to set email alerts
|

Crustal motion results derived from observations in the European geodetic VLBI network

Abstract: Geodetic VLBI observations have been performed with the European geodetic VLBI network since early 1990 on a regular basis. The purpose of these observations is to determine crustal motion in Europe and to establish a stable reference frame for other space geodetic techniques. Over the years the size of the network and the number of participating stations has steadily increased. Today, the network extends from the island of Sicily in the south to the island of Spitsbergen/Svalbard in the north and from the Ibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Geodetic VLBI observations in Europe, including the VLBI station of Madrid, have been performed on a regular basis since the early 1990s. They indicate a negligible velocity of Madrid with respect to Wettzel, located on stable Europe (0.1 ± 0.3 mm/yr; HAAS et al, 2000). The analysis of the ITRF2000 velocity field, that includes these VLBI measurements, confirms this result (Fig.…”
Section: The Iberian Peninsulasupporting
confidence: 74%
“…Geodetic VLBI observations in Europe, including the VLBI station of Madrid, have been performed on a regular basis since the early 1990s. They indicate a negligible velocity of Madrid with respect to Wettzel, located on stable Europe (0.1 ± 0.3 mm/yr; HAAS et al, 2000). The analysis of the ITRF2000 velocity field, that includes these VLBI measurements, confirms this result (Fig.…”
Section: The Iberian Peninsulasupporting
confidence: 74%
“…Nevertheless, evidence for younger tectonics includes the occurrence of Quaternary volcanism and thermal springs along N-S regional faults in the northern part of Spitsbergen (SKJELKVALE et al 1989;VÅ GNES and AMUNDSEN 1993;HJELLE et al 1999) and the existence of moderate to strong magnitude earthquakes (MITCHELL et al 1990). GUEGUEN et al (2003) and KUMAR and SINGH (2012) have found in the NW Svalbard (Ny Å lesund) an uplift rate from geodetic measurements (above 6 mm/year) higher than those predicted by post-glacial rebound models (lower than 2 mm/year, MITROVICA et al 1994;SOUDARIN et al 1999;HAAS et al 2000), and suggested a tectonic contribution related to active/recent faults in the Brøggerhalvøya.…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%
“…Many space geodetic techniques have the sensitivity to recover horizontal deformation components due to post-glacial rebound (James and Lambert, 1993;Mitrovica et al, 1993;Argus et al, 1999;Campbell and Nothnagel, 2000;Haas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%